THE ANALYSIS OF LAPSE RATE PROFILE IN THE SITE CANDIDATE OF NUCLEAR POWER PLANT (NPP) AT GOSONG BEACH, BENGKAYANG REGENCY– WEST KALIMANTAN - Deni Septiadi; Agung Hari Saputra; Rista Hernandi Virgianto; Arif Yuniarto; Muhammad Elifant Yuggotomo (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2022)
The lapse rate profile in the site candidate for the Nuclear Power Plant (NPP) at Gosong Beach Bengkayang, has been investigated to obtain a description of the lability of the atmosphere and upper air as part of a meteorological aspect safety study in the plan to develop a NPP site. The study of the lapse rate was carried out using air data on the reanalysis of the Global Data Assimilation System (GDAS) by extracting air temperature data at each altitude level so as to obtain a lapse rate of up to 25 km. Daily data was processed during 2021 and transformed in the monthly average profile data to describe the lapse rate profile in January – December 2021. Tropopause was identified with average altitude about 16.6 km and stratosphere at 20.5 km with a lapse rate about -0.21 ℃/100 m. The surface layer to 200 m have lapse rate from 0.7 ℃/100 m - 0.9 ℃/100 m at 00.00 Universal Time Coordinated (UTC) and 0.5 ℃/100 m -0.6 ℃/100 m at 12.00 UTC